Pathophysiological Mechanisms of Neurogenic Shock - Moscote-Salazar, Luis Rafael; Janjua, Tariq; Florez-Perdomo, Willian Andres; Rukadikar, Charushila; Agrawal, Amit (Indian Journal of Neurotrauma, 2025)
Neurogenic shock is caused by damage to the sympathetic nervous system. This can have negative outcomes in the patient, leading to excessive vasodilation, hypotension, and poor circulation. Spinal or brain damage usually continues. Disturbance in autonomous control, reduction in norepinephrine, inflammation, and excess nitrogen oxides are exacerbated. Compensation mechanisms often fail and highlight the need for improved treatment.
Keywords: neurogenic shock; hypotension; spinal cord injury; autonomic dysfunction; vasodilation; sympathetic nervous system; bradycardia; circulation failure; inflammation; nitric oxide